Strategies for deposition of LaFeO3 photocathodes: improving photocurrent with a polymer template - Freeman,E; Kumar,S; Celorrio,V; Park,MS; Kim,JH; Fermin,DJ; Eslava,S (Sustainable Energy and Fuels, 2019)
Renewable and sustainable alternatives to fossil fuels are needed to limit the impact of global warming. Using metal oxide semiconductors as photoelectrodes within photoelectrochemical cell devices, in which solar energy can be stored and ultimately used for electricity generation, is one such alternative. LaFeO3 (LFO) has been shown to be an active photocathode on illumination of visible light but is restricted by low surface area and relatively low photocurrents achieved. The work herein utilizes a spin coating deposition method with a solution of nitrate precursors combined with non-ionic polymeric surfactant (Triton X-100). This allowed for the formation of a uniform porous LFO film of high coverage on a fluorine-doped tin oxide coated substrate, through directing growth and preventing particle aggregation during film fabrication. These porous LFO films achieved an enhanced photocurrent of -161±6 µA cm-2 at +0.43 VRHE, in addition to a remarkable high onset potential of +1.4 VRHE for cathodic photocurrent. It was additionally shown that this attained film quality and activity was superior to other film fabrication methods such as doctor blading and spray pyrolysis. With this polymer templating method for LFO films, not only are higher photocurrents achieved but there are also added benefits such as better charge separation, higher efficiencies, higher specific electrochemically-active surface area and improved stability.